Study of People’s Opinion about Tanjung Lesung Tourist Destination - Yunita Ismail; Debora Vennecya (Journal of The Community Development in Asia, 2022)
Tanjung Lesung is a possible tourism attraction. This is consistent with the rising amount of investment in Tanjung Lesung's ecotourism sector, but the growth in poverty in Tanjung Lesung is not. The goal of this study is to examine people's perceptions of Tanjung Lesung. The elements that impact people's opinions will be categorized as economic, socio-cultural, and environmental. The survey approach was used to collect data for this study, with a questionnaire serving as the instrument. This study's sample size is 103 respondents chosen at random among Tanjung Lesung visitors. Descriptive and multiple regression analyses were employed in this study. The findings reveal that economic and environmental factors have a substantial effect on people's opinions. The socio-cultural factor, on the other hand, has no substantial impact on people's opinions.